Improving Students' Ability to Understand Multiplication and the Composition Method at MI Negeri 40 Pidie Using the Demonstration Method - Mulyana; Ernawati (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
This classroom action research aimed to improve students’ ability to understand multiplication and the composition method through the application of the demonstration method at MI Negeri 40 Pidie. The research was conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The subjects of this study were 26 fifth-grade students, including 14 boys and 12 girls. Data were collected through observation, tests, interviews, and documentation, and analyzed using both qualitative and quantitative descriptive methods. The results revealed that the demonstration method significantly improved students’ understanding of multiplication and number composition. Before the implementation, only 48% of students achieved the minimum mastery criterion (70). After the first cycle, this number increased to 72%, and in the second cycle, it reached 92%. The improvement occurred because the demonstration method enabled students to observe concrete examples, manipulate learning materials directly, and engage in hands-on learning that fostered conceptual understanding. Moreover, students became more active, motivated, and confident in solving multiplication problems. In conclusion, the use of the demonstration method proved effective in enhancing both cognitive achievement and learning engagement among students in mathematics learning at the elementary level.